PERSEPSI AKUNTAN PUBLIK DAN AKUNTAN PENDIDIK TERHADAP KODE ETIK AKUNTAN INDONESIA - Noor, Siti Noor; Faizah, Isti Faizah (Jurnal Analisis Bisnis Ekonomi, 2005)
The aim of this research is to investigate the empirical evidence about differential perception in public accountant and educational accountant in ethical conduct of accounting profession. Ethical conduct of accounting is norm of behavior that arrange relation between accountant with their client, between accountant with accountant either, and between profession wih human being. This research was to examine whether are there not differential perceptions between public accountant and educational accountant in the ethical conduct of accounting profession. The analysis is based on the answer from respondent where its data are gathered trough questionnaries in which it distribussion at Semarang. The sample of this research are public accountant who work in registered public accountant and educational accountant who work in university in Semarang. The respondents of this research are 65 respondents that consist of 32 respondents from public accountant and 33 respontents from educational accountant. Convenience sampling have used in this research. The method of analysis data are descriptive statistic, validity are reability, and independent sample t-test. Result showed that, the data in this research is valid and reliable. The results showed that there are not differential perceptions between public accountant and educational accountant in ethical conduct of accounting profession. The analysis perception public accountant and educational accountant in ethical conduct of accounting profession have perceptual that not different with p= 0.779, p> 0.05.